2019
DOI: 10.1111/bph.14559
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of zinc and insulin on arcuate anorexigenic proopiomelanocortin neurons

Abstract: Background and Purpose Acute insulin administration hyperpolarized, with concomitant decrease of firing rate, a subpopulation of arcuate proopiomelanocortin (POMC) and neuropeptide Y/agouti‐related peptide cells. This rapid effect on cellular activity has been proposed as a cellular correlate of insulin effects on energy balance and glucose homoeostasis. Recent evidence suggests that zinc in mammalian insulin formulations is required for the insulin‐induced inhibition of arcuate POMC neurons, while guinea pig … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…4, A to D). Consistent with previous reports (18,44,45), insulin (50 nM) hyperpolarized arcuate AgRP neurons from control mice (change of resting potential, −9.1 ± 0.8 mV; Fig. 4, E and M) and greatly reduced action potential (AP) firing frequency [artificial cerebrospinal fluid (ACSF): 1.7 ± 0.4 Hz; insulin + ACSF: 0.17 ± 0.10 Hz; *P < 0.05)] (Fig.…”
Section: Lack Of Barr1 In Agrp Neurons Inhibits Insulin-mediated Hypesupporting
confidence: 93%
“…4, A to D). Consistent with previous reports (18,44,45), insulin (50 nM) hyperpolarized arcuate AgRP neurons from control mice (change of resting potential, −9.1 ± 0.8 mV; Fig. 4, E and M) and greatly reduced action potential (AP) firing frequency [artificial cerebrospinal fluid (ACSF): 1.7 ± 0.4 Hz; insulin + ACSF: 0.17 ± 0.10 Hz; *P < 0.05)] (Fig.…”
Section: Lack Of Barr1 In Agrp Neurons Inhibits Insulin-mediated Hypesupporting
confidence: 93%
“…To identify POMC and NPY neurons with or without LepR, we generated POMC-hrGFP::LepR-cre::tdTomato (PLT) and NPY-hrGFP::LepR-cre::tdTomato (NLT) mice as previously described [41], [42], [43], [44]. Briefly, LepR reporter mice were made by mating LepR-cre mice [45] with the tdTomato reporter mouse (#007908; The Jackson Laboratory).…”
Section: Methodsmentioning
confidence: 99%
“…Our lab and others, have demonstrated that the activity of various metabolic signals either synergize or segregate into subpopulations of POMC and NPY/AgRP neurons( Fig. 3 ) [ 51 , 52 , 82 , 99 , 101 , 108 , 109 , 111 , 127 , 160 , 163 , 173 , 174 , 180 , 195 , 197 , 198 ]. For example, acute leptin receptor activity in ARH POMC neurons colocalizes with adiponectin and GLP-1 receptor (GLP-1r) activity [ 98 , 180 ].…”
Section: Metabolic Signals and Cell-type Specificity Of Hypothalamic mentioning
confidence: 99%
“…In particular, leptin, serotonin (via serotonin 2c receptors – 5-HT 2c R), adiponectin, and glucagon-like peptide 1 (GLP-1) serve to activate, while insulin inhibits POMC neurons via their cognate receptors [ 5 , 48 , 52 , 82 , 98 , 99 , 102 , 103 , 108 , 109 , 161 , 163 , 174 , 180 , 181 ]. Conversely, leptin, serotonin (via serotonin 1b receptors - 5-HT 1b R), adiponectin, insulin, and GLP-1 inhibit NPY/AgRP cells [ 5 , 13 , 48 , 98 , 99 , 103 , 111 , 127 , 163 , 190 ]. While leptin, serotonin, adiponectin, and insulin directly inhibit NPY/AgRP neurons, GLP-1 indirectly inhibits NPY/AgRP neurons via GABAergic synaptic connectivity [ 98 , 163 ].…”
Section: The Arcuate Nucleus: Pomc and Npy/agrp Neuronsmentioning
confidence: 99%
See 1 more Smart Citation